A study of sports celebrity endorsement advertising: a partial replication and extension - Dix, Steve (School of Marketing, Curtin Business School, 2010)
This research identifies key factors predicting the effectiveness of sports celebrity endorsement advertisements and examines correspondent inferences and endorser characteristics to predict factors that influence consumer attitudes toward the endorser, advertisement and brand. The study provides valuable implications to brand managers for sport celebrity endorsement and provides companies' with insight into the strategic use of their resources to gain advertising objectives and maximise return on investment with sports celebrity endorsement practices. The study used a partial replication and extension of Silvera and Austad (2004) study conducted in Norway. Using a sports celebrity endorser and self-administered questionnaires were distributed over 240 respondents. Findings showed there were no significant differences in consumer attitudes toward endorser, advertisement and brand when endorsing sports and non-sports brands. Although, the scope of research was extensive it was not without limitations. These include the use of convenience sampling, investigation of one endorser and examination of sports celebrity effectiveness in print advertisements only.